Relación del e-learning en la autoeficacia académica en estudiantes de los primeros ciclos de odontología - Acero-Condori, Lizbeth (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2024)
The objective of this research was to determine the relationship between e-learning and the academic self-efficacy of students in the early cycles. The study was a quantitative, cross-sectional, descriptive, and prospective approach, with a non-experimental design of correlational scope. The sample consisted of 120 students enrolled in the first and second academic semester of 2022-I at the Professional School of Dentistry of the National University of the Altiplano (Puno -Peru), selected through simple randomsampling. They were evaluated for learning achievement and administered two structured questionnaires. The first questionnaire assessed the electronic learning system through three dimensions: system quality, information quality, and service quality.The second questionnaire evaluated academic self-efficacy with two dimensions: satisfaction and benefits. Chi-square test was used for statistical analysis. The level of learning achievement was deemed acceptable in terms of academic performance and received good qualitative appreciation despite the survey indicating a low level of electronic learning system quality and a medium level of e-learning satisfaction. In conclusion, it was determined that there is no statistically significant relationship between e-learning and academic self-efficacy measured through learning achievement.